2013
DOI: 10.1152/ajprenal.00296.2013
|View full text |Cite
|
Sign up to set email alerts
|

1,25(OH)2D3-enhanced hypercalciuria in genetic hypercalciuric stone-forming rats fed a low-calcium diet

Abstract: (1,25D) increases urine (U) Ca to a greater extent in GHS than in controls [Sprague-Dawley (SD)]. The additional UCa may result from an increase in intestinal Ca absorption and/or bone resorption. To determine the source, we asked whether 1,25D would increase UCa in GHS fed a low-Ca (0.02%) diet (LCD). With 1,25D, UCa in SD increased from 1.2 Ϯ 0.1 to 9.3 Ϯ 0.9 mg/day and increased more in GHS from 4.7 Ϯ 0.3 to 21.5 Ϯ 0.9 mg/day (P Ͻ 0.001). In GHS rats on LCD with or without 1,25D, UCa far exceeded daily Ca i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 64 publications
2
22
0
2
Order By: Relevance
“…In the present series, serum 1,25(OH) 2 D 3 correlated with VDR immunostaining in osteoblasts from IH patients. These findings agree well with experimental data showing a 4-fold increase in the level of VDR in GHS calvarias versus controls and a greater sensitivity to 1,25(OH) 2 D 3 compared with bone from control rats (17,35). The direct correlation that we have found between VDR and Tb.N in osteoblasts in IH further reinforces the contribution of VDR to increase bone resorption.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present series, serum 1,25(OH) 2 D 3 correlated with VDR immunostaining in osteoblasts from IH patients. These findings agree well with experimental data showing a 4-fold increase in the level of VDR in GHS calvarias versus controls and a greater sensitivity to 1,25(OH) 2 D 3 compared with bone from control rats (17,35). The direct correlation that we have found between VDR and Tb.N in osteoblasts in IH further reinforces the contribution of VDR to increase bone resorption.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, there were no significant correlations between FGF-23 bone immunostaining and serum phosphate or between PTH and vitamin D. The small number of hypophosphatemic patients in the current series might have accounted for the lack of such correlation. Among the presumed mechanisms responsible for impaired bone formation in IH patients, elevated serum 1,25 (OH) 2 D 3 levels may play a role (11-14,33,34) through decreasing bone collagen synthesis (31) or increasing bone resorption (35). A greater increase in urinary calcium with 1,25D in GHS rats fed a low calcium diet has suggested that the additional urinary calcium must result from increased bone resorption because of the increased number of VDR in their bone cells (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29,33,34,37,40,43,48,[67][68][69] Ratios of 1 denote a urine at equilibrium, those .1 denote supersaturation, and those ,1 denote undersaturation. We have found excellent correspondence between calculated and experimentally measured saturation in urine and blood and in bone culture medium.…”
Section: Urine Supersaturationmentioning
confidence: 99%
“…To identify the source(s) of the increased uCa, a low-Ca diet (LCD) was utilized to remove the contribution of increased intestinal Ca absorption to the hypercalciuria. The hypercalciuria persisted in GHS either with or without additional 1,25D (30), suggesting that the increased uCa was derived from increased bone resorption. In this study we tested the hypothesis that in rats fed LCD, inhibition of bone resorption with a maximal dose of the bisphosphonate alendronate (alen) would result in equalization of uCa between GHS and SD rats.…”
mentioning
confidence: 96%